Agreement Between the Mini-Cog in the Preoperative Clinic and on the Day of Surgery and Association With Postanesthesia Care Unit Delirium: A Cohort Study of Cognitive Screening in Older Adults. (April 2021) - Tiwary, Nayan; Treggiari, Miriam M.; Yanez, N. David; Kirsch, Jeffrey R.; Tekkali, Praveen; Taylor, Cornelia C.; Schenning, Katie J.
Abstract : BACKGROUND: Cognitive impairment is common in older surgical patients and is associated with postoperative delirium. However, cognitive function is inconsistently assessed preoperatively, leading to missed opportunities to recognize vulnerable patients. We designed a prospective cohort study to assess the agreement of the Mini-Cog screening tool administered in the preoperative clinic (clinic-day test) or immediately before surgery (surgery-day test) and to determine whether a positive screening for cognitive dysfunction in the surgery-day test is associated with postoperative delirium in the postanesthesia care unit (PACU). METHODS: This was a cohort study of patients aged 65–89 years, scheduled for elective, inpatient surgery under general anesthesia between June 20, 2018 and August 3, 2018. Mini-Cog test scores were obtained during a clinic-day test and surgery-day test. The Short Confusion Assessment Method was performed in the PACU. Agreement between Mini-Cog clinic-day and surgery-day test scores was estimated using an ordinally weighted kappa statistic, κ. Multivariable logistic regression was used to determine whether there was an association between a positive screen for cognitive impairment and PACU delirium. Odds ratio analysis was performed to determine whether the Mini-Cog score was associated with PACU delirium. RESULTS: Of 128 patients meeting eligibility criteria, 80 patients were enrolled. Ten had cognitive impairment based on the Mini-Cog clinic-day test score, while 70 did not. Age, sex, race, education level, subjective memory impairment, and American Society of Anesthesiologists (ASA) physical status were equivalent in the 2 groups. The mean number of days between the clinic-day score and the surgery-day score was 8.4 days (standard deviation [SD] = 6.9). Mini-Cog clinic-day and surgery-day scores had high agreement (κ = 0.78; 95% confidence interval [CI], 0.69–0.87; P < .001), and both scores were highly predictive of PACU delirium. Patients with Mini-Cog surgery-day scores compatible with cognitive impairment (Mini-Cog scores ⩽2) had an estimated 12.8 times higher odds of PACU delirium compared to patients with normal cognitive function or Mini-Cog scores >2 (odds ratio [OR] = 12.8; 95% CI, 2.6–63.8, P = .002). Similarly, patients with Mini-Cog clinic-day test scores compatible with cognitive impairment had an estimated 29 times higher odds of PACU delirium compared to patients with normal cognitive function (OR = 29.0; 95% CI, 2.6–63.8, P < .001). CONCLUSIONS: These data support the approach of using the Mini-Cog on the day of surgery to screen for cognitive impairment in older patients. Importantly, Mini-Cog surgery-day test scores compatible with cognitive impairment (⩽2) were strongly associated with PACU delirium.